"I Discovered More than Book Knowledge": York University's Bridging Program for Women - O'Reilly, Andrea (Atlantis)

(untitled) (Mount Saint Vincent University, 2009)
This article examines York University's Bridging Program for Women from the perspectives of 37 of the program's graduates, showing how this program made possible the empowerment of women over the last quarter century. It focuses on three reoccurring themes found in the students' narratives: security, community, and validation.